NUTRIENT CONTENT OF COCOA POD (Theobroma cocoa) FERMENTATION WITH Aspergilllus niger ADDITION - Engkus Ainul Yakin; Ahimsa Kandi Sariri (Program Studi Peternakan, Fakultas Pertanian, Universitas Veteran Bangun Nusantara, 2019)
The study was conducted to determine the increase in nutrient content and decrease in the lignin content of cocoa pod fermented with Aspergillus niger. The research method used three treatments and four replications. T0 = cocoa pod fermented without the addition of Aspergillus niger, T1 = cocoa pod fermented with the addition of 1% Aspergillus niger, and T2 = cocoa pod fermented with the addition of 2% Aspergillus niger. Fresh cocoa pod was chopped in 1-2 cm size. Cocoa pod chopped and dried, some added with Aspergillus niger. The mixture is put into an aerobic container for 7 days. The variables observed included dry matter, crude protein, crude fiber, and crude fat. This study was designed using a complete randomized design research design with one-way ANOVA analysis. Significant variables were followed by Duncan's multiple range test (Duncan multiple range test / DMRT). The results of the study showed significantly different results in all treatments. It was concluded that the fermentation with addition Aspergillus niger until 2% decrease crude protein, crude fiber, and crude fat on cocoa pod fermentation.